Platelet Glycoprotein Ⅵ: A Novel Target for Antithrombotic Therapy in Cardiovascular Disease - Menglu Liu; Xueyan Zhao; Hanjia Gao (Cardiology Discovery)
Abstract. Platelets play an important role in thrombosis caused by acute coronary syndrome and stroke. As the main platelet collagen receptor, platelet glycoprotein Ⅵ (GPⅥ) is an important modulator in the activation and aggregation of platelets at vascular injury sites. Recently, GPⅥ has been identified as a potent antithrombotic target. The structure, properties, functions, and downstream signaling of GPⅥ are reviewed; its relationship with bleeding, thrombosis, and other diseases are discussed; and potential of GPⅥ as a future antiplatelet therapeutic target is summarized in this article.